Mortality of necrotizing fasciitis: relative influence of individual and hospital‐level factors, a nationwide multilevel study, France, 2007–123. (9th October 2017) - Audureau, E.; Hua, C.; de Prost, N.; Hemery, F.; Decousser, J.W.; Bosc, R.; Lepeule, R.; Chosidow, O.; Sbidian, E.
Summary: Background: Necrotizing soft‐tissue infections (NSTI) are rare, life‐threatening conditions. Objectives: To assess whether admitting hospital characteristics were associated with NSTI mortality. Methods: We studied the French nationwide hospital discharge database (retrospective national cohort). All patients admitted in the period 2007–12 with an International Classification of Diseases 10 code of necrotizing fasciitis were eligible. We extracted data on the patients (age, sex, intensive care unit admission, comorbidities) and hospitals (public vs. private proprietary; for public hospitals, teaching, yes/no; and number of NSTI admissions, ≥ 3 NSTI cases/year, yes/no). Multivariable analyses were performed to identify independent predictors of 28‐day mortality and in‐hospital mortality using mixed logistic regression and Cox proportional hazards models, respectively. Results: We identified 1537 patients (915 males) with a median age of 60 years (interquartile range 48–75), admitted to 326 hospitals, public (82%) and admitting < 3 NSTI cases/year (93%). Overall, 364 patients died [23·7%; 95% confidence interval (CI) 21·6–25·9]. Patients treated in public teaching centres with ≥ 3 NSTI cases annually had lower 28‐day mortality (adjusted odds ratio 0·68; 95% CI 0·46–0·99; P = 0·045) and in‐hospital mortality rates than patients treated in local hospitals, even after adjusting for potentially relevant individual risk factors. No significant association was found between mortality and interhospital transfer. Conclusions: Our findings highlight an increased survival in teaching centres with high‐volume NSTI procedures. If confirmed in other settings, these findings reinforce the importance of expertise in early diagnosis and management of this condition. Abstract : What's already known about this topic? Necrotizing soft‐tissue infections (NSTI) are rare, life‐threatening conditions. At the individual level, risk factors for in‐hospital mortality have been identified (older age, female sex and comorbidities). Few studies regarding the associations between hospital characteristics and NSTI mortality, with special attention to referral hospitals are available. What does this study add? Patients treated in referral hospitals had lower short‐term mortality rates than did patients in community hospitals, after adjusting for known risk factors. No association between interhospital transfer and survival was found. If confirmed in other settings, these findings support the early transfer of patients with suspected or diagnosed NSTI to referral centres, where a multidisciplinary approach can be implemented by experienced healthcare professionals, to maximize short‐term survival. Plain language summary available online Respond to this article